Management of complicated diverticulitis of the colon. Issue 1 (28th September 2017) - Tochigi, Toru; Kosugi, Chihiro; Shuto, Kiyohiko; Mori, Mikito; Hirano, Atsushi; Koda, Keiji
Abstract: Diverticular disease of the colon occurs quite frequently in developed countries, and its prevalence has recently increased in Japan. The appearance of diverticulosis increases with age, although mostly remaining asymptomatic. Approximately 20% of cases require treatment. As the Western lifestyle and number of elderly people increase, the need for medical treatment also increases. Computed tomography (CT) is the gold standard for diagnosing diverticulitis. Complicated diverticulitis is classified by the size and range of abscess formation and the severity of the peritonitis. Each case should be classified based on clinical and computed tomography (CT) findings and then treated appropriately. Most patients with uncomplicated diverticulitis (stages 0–Ia) can be treated conservatively. Diverticulitis with a localized abscess (stages Ib–II) is generally resolved with conservative treatment. If the abscess is larger or conservative treatment fails, however, percutaneous drainage or surgery should be considered. Operative treatment is considered standard therapy for severe diverticulitis with perforation and generalized peritonitis (stages III–IV). Colonic diverticulitis treated conservatively frequently recurs. Elective surgery after recovery should be considered carefully and decisions made on a case‐by‐case basis. Because cases of colonic diverticulitis will undoubtedly increase in Japan, it is likely that we will be confronted with increasing numbers of treatment decisions. We therefore need to have a systematic strategy for treating the various stages of colonic diverticulitis appropriately. We herein review the management of complicated diverticulitis.